Describing the State of Social Tolerance in the Social Space of Isfahan - Masoome Kermanshahi; Seyed Ali Hashemianfar; Fereydoun Vahida (توسعه پایدار شهری)
Urban social life is a mixture of cultures, religions, and ethnicities. On the other hand, due to the ever-expanding social relationships, tolerating differences and nonconformities has become a critical matter. Social tolerance, in conjunction with concepts such as respect and acceptance of diversity, is a tool for regulating the interactions of people and different groups with each other. Anything that has the potential to improve social relations will lead to improved quality of life and social health, guiding society to realize the goals of sustainable development. Based on the theories of Durkheim, Adorno, and Horkheimer, the present study aimed to describe the various social factors affecting social tolerance among citizens of Isfahan, Iran. Subsequently, 461 individuals from the target population were selected by stratified sampling utilizing the G*Power software. The collected data from the questionnaires were then analyzed using SPSS 22. The results showed a direct and significant relationship between religiosity (0.308) and cultural intelligence (0.383) with social tolerance. On the other hand, variables of authorities (-0.250) and stereotype (-0.151) showed a significant, inverse relationship with social tolerance.